ON. Off. On. Off. Light Intermittence as a creation practice in the 1960s (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2021)
A segmented conception of time in the modern era contributes to producing progressively a clipped and intermittent grammar within the field of artistic production. Due to certain movements, such as the Flicker Film in the 60s, this practice will be taken to the extreme leading to works exclusively composed by the flickering of light.
Keywords: Intermittence; Flicker Film; Epilepsy; Peter Kubelka; Tony Conrad